Pengaruh Employee Engagement dan Tingkat Pendidikan terhadap Kinerja Mitra Badan Pusat Statistik - Yossi Adriati (Universitas Mercu Buana Yogyakarta, 2022)
The purpose of this study was to determine and analyze the employee engagement and partner performance of BPS-Statistics of Ogan Komering Ilir Regency. This study uses primary data from 64 respondents who are the partner sample of BPS- Statistics of Ogan Komering Ilir Regency. This research is quantitative by using descriptive analysis and inferential analysis to answer research problems. The model used to see the relationship between employee engagement and the highest level of education with performance is multiple linear regression with dummy variable. The independent variable in this study was employee engagement and the highest level of education, while the dependent variable was the partners performance of BPS-Statistics of Ogan Komering Ilir Regency. The results of this study are the condition of employee engagement and partner performance of BPS-Statistics of Ogan Komering Ilir Regency is good. The variable employee engagement and the highest level of education simultaneously significantly affect partner performance. The partial test resulted in a conclusion, the employee engagement variable had a positive and significant effect on the partners performance of BPS-Statistics of Ogan Komering Ilir Regency, while the variable of the highest education level had a positive but not significant effect on the partners performance of BPS-Statistics of Ogan Komering Ilir Regency.